Surface morphology of zirconium after treatment with high-frequency currents. (15th October 2018) - Koshuro, Vladimir; Fomina, Marina; Voyko, Aleksey; Rodionov, Igor; Zakharevich, Andrey; Skaptsov, Aleksandr; Fomin, Aleksandr
Abstract: Coatings of zirconia were prepared by oxidation of zirconium grade E110 using induction heat treatment (IHT) with high-frequency currents. The IHT was performed at temperatures within 600–1200 °C for 30–300 s. According to the results of scanning electron microscopy, X-ray diffraction, energy dispersive analysis, and nanoindentation, zirconia coatings with high hardness (about 17 ± 0.4 GPa) and elastic modulus (about 270–320 GPa) were formed on zirconium surface after semi-rough turning followed by IHT at 1000 °C for 30 s. The coatings consisted of nanocrystals with an average size of 37 ± 2 nm. Zirconia coatings with high morphological heterogeneity (nanocrystals with an average size of 45 ± 2 nm), moderate hardness (about 4.5–5.5 GPa) and high elastic modulus (about 272–285 GPa) were formed on zirconium surface after abrasive blasting followed by IHT at 1000 °C for 30 s.